2016
DOI: 10.1097/jcn.0000000000000217
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Massage on Blood Pressure in Patients With Hypertension and Prehypertension

Abstract: This systematic review found a medium effect of massage on SBP and a small effect on DBP in patients with hypertension or prehypertension. High-quality randomized controlled trials are urgently required to confirm these results, although the findings of this study can be used to guide future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
1
13
0
3
Order By: Relevance
“…Study results of Liao et al . 's (2016) showed that massage contributes to significantly enhanced reduction in SBP and as compared with control treatments in patients with hypertension and prehypertension[ 23 ] Chen et al . 's (2016) meta-analysis study demonstrated a medium effect of massage on SBP and a small effect on DBP in patients with hypertension or prehypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Study results of Liao et al . 's (2016) showed that massage contributes to significantly enhanced reduction in SBP and as compared with control treatments in patients with hypertension and prehypertension[ 23 ] Chen et al . 's (2016) meta-analysis study demonstrated a medium effect of massage on SBP and a small effect on DBP in patients with hypertension or prehypertension.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review has highlighted that massage therapy significantly reduced both systolic blood pressure and diastolic blood pressure with no reported adverse effects among patients with hypertension and prehypertension when compared with control groups which included the use of placebo, no treatment, standard care, or any active treatment unrelated to massage therapy. 18 While massage is safe in general, it is not entirely risk free and the technique should be optimized to prevent adverse events. 19 Alt-text: Box 1
Effectiveness of ginseng in improving cognitive function among healthy older people Dementia is a prevalent problem among older people, characterized by progressive cognitive impairment which lowers the ability to perform daily activities and increases the likelihood of behavioral disturbances.
…”
Section: Main Textmentioning
confidence: 99%
“…A recent systematic review has highlighted that massage therapy significantly reduced both systolic blood pressure and diastolic blood pressure with no reported adverse effects among patients with hypertension and prehypertension when compared with control groups which included the use of placebo, no treatment, standard care, or any active treatment unrelated to massage therapy. 18 While massage is safe in general, it is not entirely risk free and the technique should be optimized to prevent adverse events. 19 …”
Section: Main Textmentioning
confidence: 99%
“…Kardiyovasküler egzersiz ile aynı etkiyi yapan masaj uzun süre endotelyal koruma ve gevşeme sağladığından kan basıncının düşmesini sağlamaktadır. Masajın, kan basıncı üzerine etkisi değerlendirildiğinde, vücuttaki kan akışını dengelemesi ve gevşeme cevabının bir sonucu olduğu yapılan meta-analiz çalışmaları ile desteklenmektedir (10,12).…”
Section: Masajın Kan Basıncı üZerine Etkisiunclassified
“…Hipertansiyon tedavisinde bireylerin destekleyici olarak kullandığı tamamlayıcı ve bütünleşik (integratif) tedavi yöntemlerinden biri olan masaj birçok çalışmada farklı yöntemlerle uygulanmış ve kanıtları paylaşılmıştır. Masajla ilgili yapılan çalışmalar incelendiğinde; masajın anksiyete düzeyini, kan basıncını, solunum hızını azalttığı saptanmıştır (12,13,16). Bunların yanı sıra masajın uyku problemleri, baş ağrısı, sırt ağrısı, gerilimi azaltma ve kas kramplarını rahatlatma gibi etkilerinin de olduğu belirtilmektedir.…”
Section: Hipertansiyonlu Bireylerde Masajın Kullanımıunclassified